INFLUENCE OF CROPS, WHICH ARE INCLUDED IN THE SYSTEM OF SHORT-TERM CROP ROTATION ON THE AMOUNT OF NUTRIENT IN THE SOIL - Uzakbay E. Ismailov ,; Dilfuza B. Kutlimuratova, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Soils of the Republic of Karakalpakstan are salty and low in fertility. In such soils, measures should be taken to improve the meliorative condition of soils and increase soil fertility for receiving high yield from agricultural crops. In order to increase soil fertility, it is better to use organic fertilizers. Field experiments have been carried out to determine the influence of crops which are included in the system of short-term crop rotation on the amount of nutrients in the soil. In this case, in determining the influence of mung bean, sesame and soybean, which were sown before winter wheat, on the amount of nutrients in the soil, in the system of crop rotation 1: 2, cotton: past crop + mung bean for siderate + 20 t / ha of manure + winter wheat, when it was sown in the method of winter wheat the amount of humus in the soil was determined to increase by 0.40 %.